MENGEMBANGKAN KEMANDIRIAN DAN MOTORIK KASAR MELALUI PROBLEM BASED LEARNING, DIRECT INSTRUCTION DAN PERMAINAN HOPSCOTCH PADA KELOMPOK B - Aryani, Meliya; Amelia, Rizky (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The problem in this study is the low gross motor skills of children, as indicated by suboptimal body movement coordination, balance, and children's ability to follow the rules of physical games. This is caused by the limited variety of learning activities that directly involve children's physical activity, resulting in children being less active in participating in learning. This study aims to describe teacher activities, analyze children's activities and independence, and analyze the results of children's gross motor development. This research uses a qualitative research approach with a classroom action research type conducted in class B at TK Amalia Banjarmasin. The results of this study show that teacher activities fall into the very good category, children's activities fall into the very active category, children's independence falls into the very independent category, and the results of children's gross motor development fall into the Very Good Development category. Based on these findings, it can be concluded that the combination of Problem Based Learning (PBL) Model, Direct Instruction, and Hopscotch Game Media in learning activities can develop the activity, independence, and gross motor skills of children in Group B at Amalia Kindergarten Banjarmasin. It is recommended for kindergarten principals, teachers, and future researchers to use this as a reference and source of information to improve learning for children.